Postpartum Gymnastics with the Process of Uterine Involution in the Regional General Hospital of Central Sulawesi - Ula, Zumrotul; Munir, Wahidah; Sarofah Ningsih, Eka; Ajeng Wijayanti, Lumastari; Sima, Yenny; Fatimah, Sitti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Many factors can affect the involution process including postpartum exercises, breastfeeding, early mobilization, nutritional status, parity and age. One of the factors that influence uterine involution is postpartum exercise and parity. Mothers who do not do puerperal exercises have a slower involution process and high parity involution process becomes slower, because the more often pregnant, the uterus will often experience strain. The purpose of this study was to determine the relationship between postpartum exercises and parity with the process of uterine involution at the Regional General Hospital of Central Sulawesi Province. The design of this study used the Surveyanalytic method with a Cross Sectional approach. Cross Sectional is a research design by measuring and observing the independent and related variables only once at the same time and at the time of the study. This research was conducted at Central Sulawesi Provincial Hospital. The results of the analysis show that the results of the statistical analysis test using the Chi-square test obtained a value of ρvalue = 0.000 (ρ < 0.05), where Ha is accepted and H0 is rejected, which means there is a significant relationship between parity and the process of involutionouteri. The conclusion is that there is a relationship between postpartum exercises, parity with the involution process at the Central Sulawesi Provincial General Hospital. This is because postpartum exercises help heal the uterus, abdomen, and hip muscles that have been traumatized and accelerate the return of these parts to normal form while parity, due to the state of the uterus which is increasingly pregnant uterus is also often stretched.